Menatap Sustainable Development pada Kereta Cepat - Hartanto Rosojati; Shanti Darmastuti; Darin Atiandina (Universitas Mataram, 2023)
The government has set the construction of the first high-speed train in Indonesia by building High Speed Rail for the Jakarta-Bandung line. The aspect of financing and the potential for economic income is always become in the spotlight, as well as the urgency. Beyond that, it is important to see the presence of the high-speed train not only from its economic growth, or the calculation of profit and loss, but also from economic development as well as sustainable development. This study, which is based on literature studies and is also supported by field observations, shows that the construction of the high-speed train can be an entry point for laying down the concept of sustainable development. This study also shows that the Jakarta-Bandung high-speed train is able to create employment, and creates a sustainable city development, especially in areas outside the city center, such as Tegalluar Station which is outside the urban core area. By creating support and opportunities from this potential, as well as ensuring good governance with quality policies and laws that are in accordance with sustainable development, the Jakarta-Bandung high-speed rail project is a milestone towards achieving sustainable development goals.